известна формула: V(x^2) = |x| 1)...= |1-V26|+|2-V26|+|3-V26|+|4-V26|+|5-V26|+5*|6-V26| = V26 - 1+V26 - 2+V26 - 3+V26 - 4+V26 - 5+5*6 - 5V26 = 30-15 = 15 2a) или х-3=2х или х-3=-2х х=-3 или х=1 2б) можно по-разному решать... например, так: V(x-3)^2 > V(2x)^2 x^2 - 6x + 9 > 4x^2 x^2 + 2x - 3 < 0 ---> x э (-3; 1)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
известна формула: V(x^2) = |x| 1)...= |1-V26|+|2-V26|+|3-V26|+|4-V26|+|5-V26|+5*|6-V26| = V26 - 1+V26 - 2+V26 - 3+V26 - 4+V26 - 5+5*6 - 5V26 = 30-15 = 15 2a) или х-3=2х или х-3=-2х х=-3 или х=1 2б) можно по-разному решать... например, так: V(x-3)^2 > V(2x)^2 x^2 - 6x + 9 > 4x^2 x^2 + 2x - 3 < 0 ---> x э (-3; 1)